CHANGES IN THE BEHAVIOR OF FISHES AND INSECTS BEFORE EARTHQUAKES AT THE GARM TEST SITE - Deshcherevskii A.V.; Sidorin A.Ya. (My University, 2004)
Time series of data on variations in the electric activity of four Nilotic species of weakly electric elephant-snout fish Gnathonemus leopoldianus and motion activity of two catfishes Hoplosternum thoracatum and two groups of Columbian cockroaches Blaberus craniifer were analyzed. A detailed analysis of the statistical structure of the total array of parametric time series obtained in the experiment showed that the behavior of all animals shows a strong temporal variability. All calculated parameters are unstable and subject to frequent changes. A comparison with seismicity demonstrated that the probability of reconstructions in the dynamics of calculated parameters increases before the closest earthquakes (hypocenter distance is comparable with the source size). However, these reconstructions do not differ from their counterparts in the structure of parametric series without any correlation with the seismicity.